Application of Buck Rotation System to Improve the Quality of Goat Phenotypes and Genotypes in KUBE X Sejahtera 005 Farmer Group - Nugraheni, Yudhi Ratna; Prastowo, Joko; Ariyadi, Bambang; Awaludin, Aan; Muhamad, Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Goats are the leading livestock commodity in the Samigaluh sub-district. The goat population in the Samigaluh sub-district was 15,866 goats (16.7%) of the total goat population in Kulon Progo which reached 95,257 goats. Peranakan Ettawa (PE) goats are widely kept and bred because of their high quality and price value, some are crossbred with local goats called Bligon. Limited access and quality bucks are one of the obstacles in breeding and improving the quality of goats, the use of artificial insemination (AI) in goat breeding has a low success rate. This community service (PkM) aims to educate and foster awareness and the active role of farmers in maintaining and improving the quality of goats from the reproduction side. The PkM partner is the KUBE Sejahtera X Binangun 005 livestock group which is a productive community group within the scope of the UGM assisted village in Sidoharjo village. Transfer of knowledge and skills has been carried out using counseling methods, interactive discussions, and practice in selecting superior males and applying the Buck Rotation System to maintain and improve the quality of goats phenotypically and genotypically. Evaluation of PkM by taking the parameters of knowledge and skills of farmers in assessing and selecting superior bucks and recording reproduction by implementing the Buck Rotation System. Results achieved, the training participants of the KUBE Sejahtera X Binangun 005 farmer group understand the importance of reproductive health, reproductive recording, and the impact of inbreeding and can judge and select bucks by SNI 7352:2008.